Labour and economic dimension in the formation of Spanish architects - Echarte Ramos, Jose María (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
In 2013 Peggy Deamer, president of The Architect Lobby, described in a synthetic manner the relation that Architects stablish with the concept of work: “We don’t believe we do work”. Taking as a starting point this particular self-perception of architecture professionals, the present article will be divided in two parts, the first will study the distancing of Spanish architects from the basic economic structures in their activity and among them and mainly, those associated to work. These would be characterized as fundamental elements in which to ground their relation with a progressively globalized world in which the economic dimension is, if not a priority, at least a fundamental one. The second part will search for the origin of this distancing in the formative processes of architects, trying to analyse the very evolution of the concept of immaterial work and its presence in the university, in the capitalist model of flexible accumulation dominant in the western world and its translation into the conception of architecture as profession.